Línea de investigación en psicofarmacología de la cocaína y el etanol en ratas y ratones. - Santacruz, María del Pilar (Acta Colombiana de Psicología, 1998)
I present a brief summary of the research, about two drugs of great abuse in Colombia: Cocaine and alcohol, carried out at Universidad Católica de Colombia’s laboratory of experimental psychology. By means of animal model, we have evaluated the effects of different doses of cocaine and alcohol (0.1,1.0,10 y 20,mg/kg) on several parameters of aggressive, emotional, and social behavior in adult female and male rats and mice, as in sons of addicted mothers along gestation time. Moreover we have assessed the effects of acute administration (one injection), chronic administration (ten to twelve consecutive injections), withdrawal syndrome with the same parameters, and long term persistence of pharmacological effects. The results of the research are presented, as well as the titles of investigations recently started .